Preserving on paper : seventeenth-century Englishwomen's receipt books - Kowalchuk, Kristine, 1974- (Studies in book and print culture., 2017)
Preserving on Paper is a critical edition of three seventeenth-century receipt books-handwritten manuals that included a combination of culinary recipes, medical remedies, and household tips which documented the work of women at home.